(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The industrial control analysis either neglects systemic versatility entirely, or only takes into consideration the flexibility of manipulation links. If the joint elasticity impact of the joint is prominent, there could be major errors in the gross motion regulation. This paper proposes an effective control system to offset movement errors created by both connection and versatility simultaneously the thesis starts off by modeling a versatile joint and by using the Lagrange formulation in three hypotheses about the complex coupling between the ties and the actuators, parallel manipulator movements are obtained both for actuator variables and joint variables. As a case example, a three-degree of freedom is simulated, taking into account the joint versatility of this study, by two legged planar parallel manipulators Flexible seals, Flexible joint principles, Flexible joint types, Dynamics of the manipulator, Parallel handler, serial handling compared, Parallel handler Parallel handler applications, Flexible joints parallel manipulator, Flexible mutual Stewart platform